An experimental study of initial flaws in thin sheets of 2024 aircraft aluminium alloy. Issue 2 (13th May 2014) - Zhuang, Wyman; Liu, Qianchu; Smith, Cathy
Abstract : Purpose: – One of the challenges in the prediction of fatigue crack growth is to identify representative initial flaws and defects that can cause fatigue crack initiation and subsequent crack growth. Representative initial flaws identified from this experimental study provided an essential input for the fatigue life assessment programme of the PC-9/A training aircraft currently in service. The paper aims to discuss these issues. Design/methodology/approach: – This paper addresses this challenge with a critical literature review and experimental assessment of initial flaw types that may cause fatigue crack initiation, by fatigue testing and fractography analysis using optical microscope and scanning electron microscopy (SEM). Findings: – With a focus on aluminium alloy (AA) 2024-T3 thin sheet, the results cover various discontinuities from microstructural constituent particles inherent from the material process to macrostructural defects and surface discontinuities (such as burrs and machining marks) introduced during the production of airframes. It was found that most fatigue cracks originated from the bore surface discontinuities of rivet holes in the PC-9 vertical stabiliser thin panels rather than microstructural material defects of AA2024-T3 inherent from the material process. Research limitations/implications: – The experimental study has found that quantifying fatigue initial flaw sizes which resulted from poorly finished fastener holes with arbitrary discontinuities at the surface is a challenging topic. This topic is under the current investigation using a statistics based analysis of initial flaws in the prediction of fatigue crack growth. Practical implications: – The results obtained from this experimental study provided an essential input for the empennage and aft fuselage recertification and life assessment programme for the PC-9/A training aircraft currently in service. Originality/value: – This experimental study examined AA2024-T3 thin skin panels from two different PC-9/A aircraft. The post-test failure analysis using optical microscope and SEM found that machining defects dominate fatigue crack initiation that can result in subsequent crack propagation.